Le point de vue de l’Inspecteur général des Institutions financières - Bouchard, Jean-Marie (Assurances, 1988)
The point of view of the Inspector General of Financial Institutions on AIDS, an insurable risk?, is indeed interesting. The author is well versed on AIDS, how it is transmitted, and the number of carriers of the virus in the world. He looks at insurance claims, the role of insurers, legislation, the notion of discrimination, screening, etc. How are insurance companies reacting and what, in fact, are insurers doing? This, basically, is the question discussed in this article, a question which presents a major role in Mr. Bouchard's function, that is, consumer protection or protection of the clients of insurance companies.